Pengaruh Kualitas Layanan terhadap Kepuasan Pelanggan pada Elegant Salon di Kota Padang - Tonapa, Jeny Cartika; Nurcahayani, Imas; Dewi, Siska Miga (Lembaga Yasin AlSys, 2025)
The salon industry in Padang City is experiencing rapid development along with the increasing public awareness of self-care and appearance. In an increasingly fierce competitive situation, service quality is a key factor in determining customer satisfaction and their loyalty. This study aims to analyze the effect of service quality provided by Elegant Salon on customer satisfaction. The approach used in this research is quantitative with descriptive and explanatory designs. The research sample consisted of 100 customers selected by purposive sampling, and data were collected through a questionnaire that measured service quality based on the five dimensions of SERVQUAL (reliability, responsiveness, assurance, empathy, and physical evidence) and the level of customer satisfaction. The collected data were analyzed using descriptive statistics and simple linear regression tests. The results showed that service quality has a positive and significant influence on the level of customer satisfaction, with the dimensions of reliability and empathy being the most influential factors. The implication of this research is to provide recommendations to Elegant Salon to improve service quality, especially in dimensions that have a major effect on customer satisfaction, in order to retain customers and increase competitiveness in a competitive market.